2023
DOI: 10.1007/s40843-022-2328-8
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and self-healing conductive hydrogels fabricated from cationic cellulose nanofiber-dispersed liquid metal for strain sensors

Abstract: The emergence of liquid metal (LM) emulsion as a soft multifunctional filler brings a new opportunity for fabricating hydrogel-based strain sensors with multifunctional properties. However, the extremely large surface tension and high density of LMs inhibit emulsification. Herein, we demonstrated a strategy for stabilizing LM emulsions using cationic cellulose nanofibers (CCNFs) to encapsulate LM droplets through strong electrostatic attraction with LM. By inducing acrylic acid (AA) polymerization in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Recently, it was reported that the high surface tension of liquid metals is solved by using cationic cellulose nanofibers (CCNFs) to prepare a conductive hydrogel (CCNFs-LM-PAA) with excellent electrical conductivity. 61 Hydrogen bonding and electrostatic interaction between CCNFs and Ga prevent precipitation or aggregation. With the increase of Ga, the maximum strain decreases and the maximum stress increases, but the conductivity of the hydrogel is not significantly affected, and finally a conductivity of 1.54 S m −1 is achieved.…”
Section: Properties Of Conductive Hydrogelsmentioning
confidence: 99%
“…Recently, it was reported that the high surface tension of liquid metals is solved by using cationic cellulose nanofibers (CCNFs) to prepare a conductive hydrogel (CCNFs-LM-PAA) with excellent electrical conductivity. 61 Hydrogen bonding and electrostatic interaction between CCNFs and Ga prevent precipitation or aggregation. With the increase of Ga, the maximum strain decreases and the maximum stress increases, but the conductivity of the hydrogel is not significantly affected, and finally a conductivity of 1.54 S m −1 is achieved.…”
Section: Properties Of Conductive Hydrogelsmentioning
confidence: 99%
“…Flexible pressure sensors typically consist of a flexible substrate, active materials, and electrodes . Commonly used flexible substrate materials include polydimethylsiloxane (PDMS), thermoplastic polyurethane (TPU), and poly(acrylic acid) hydrogel . Among them, the electrospun TPU nanofiber film has the advantages of high porosity, large surface area, and good air permeability, making it a candidate material for flexible substrates.…”
Section: Introductionmentioning
confidence: 99%
“…They can perfectly adapt to soft human skin because of their high similarity with soft biological tissues . To date, many hydrophilic polymers and conductive materials have been used to fabricate conductive hydrogels with various compositions and structures by directly mixing them before inducing the gelatinization of the polymers. Because sensing performance and self-healing and mechanical properties always determine the reliability and lifetime of strain sensors in related applications, , the development of self-healing conductive hydrogels with high sensing performance and good toughness is highly desirable. Moreover, the adhesiveness is also important for the application of hydrogel-based strain sensors.…”
Section: Introductionmentioning
confidence: 99%